2020
DOI: 10.2147/dddt.s278892
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric Absorptive Microsampling as a Sampling Alternative in Clinical Trials and Therapeutic Drug Monitoring During the COVID-19 Pandemic: A Review

Abstract: An infectious disease, COVID-19, caused by a new type of coronavirus, has been discovered recently. This disease can cause respiratory distress, fever, and fatigue. It still has no drug and vaccine for treatment and prevention. Therefore, WHO recommends that people should stay at home to reduce disease transmission. Due to the quarantine, FDA stated that this could hamper drug development clinical trial protocols. Hence, an alternative sampling method that can be applied at home is needed. Currently, volumetri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 50 publications
0
25
0
Order By: Relevance
“…The pandemic necessitated access to testing that can be conducted safely, in other words, avoiding the need for travel to a hospital or clinic, resulting in drive through and at home testing options. Although most at home testing has been noninvasive (self-sampling using a nasal swab), several COVID-19 clinical trials have included in-home collection of blood samples for serology testing, using volumetric absorptive microsampling (VAMs) and Tasso blood sampling devices [12][13][14][15]. This demonstrates the utility of in-home or patient centric blood sampling devices.…”
Section: Adoption Of Patient Centric Samplingmentioning
confidence: 99%
“…The pandemic necessitated access to testing that can be conducted safely, in other words, avoiding the need for travel to a hospital or clinic, resulting in drive through and at home testing options. Although most at home testing has been noninvasive (self-sampling using a nasal swab), several COVID-19 clinical trials have included in-home collection of blood samples for serology testing, using volumetric absorptive microsampling (VAMs) and Tasso blood sampling devices [12][13][14][15]. This demonstrates the utility of in-home or patient centric blood sampling devices.…”
Section: Adoption Of Patient Centric Samplingmentioning
confidence: 99%
“…Prior to the COVID-19 pandemic, remote sampling using Mitra devices was beginning to gain good traction, with a number of clinical trials reported in the literature. Sixteen of these trials were listed in a recent review by Y Harahap and colleagues [ 47 ]. Additionally, a paper has recently been published by AstraZeneca, discussing the benefits of patient-centric sampling using Mitra devices (and other remote solutions) to allow for a mixed approach to sample collection for clinical trials.…”
Section: Using Vams In Covid-19 Clinical Trialsmentioning
confidence: 99%
“…As a minimally invasive approach, volumetric absorptive microsampling (VAMS), an enhanced development of dried blood spot sampling, allows collecting a small defined volume (10–30 ÎŒL) of capillary blood from the patient’s fingertip [ 18 ] which is subsequently air-dried and sent to the analytical laboratory using normal post. In contrast to venous blood, using dried capillary blood as matrix for TDM has several advantages: (i) the samples can be collected in a home-based setting [ 19 ], (ii) the collected blood samples do not have to be cooled or further processed [ 19 , 20 ], and therefore (iii) the samples can be shipped to the laboratory via normal post [ 19 , 20 ]. The main advantages of VAMS over dried blood spots sampling are the collection of defined blood volumes (10–30 ÎŒL), its independence of hematocrit values [ 18 ], and its easy handling.…”
Section: Introductionmentioning
confidence: 99%